Clinical profile and treatment outcome of chronic pancreatitis in children: a long-term follow-up study of 156 cases. (3rd July 2017) - Poddar, Ujjal; Yachha, Surender Kumar; Borkar, Vibhor; Srivastava, Anshu; Saraswat, Vivek A.
Abstract: Aim: There is a paucity of literature in pediatric chronic pancreatitis (CP) and most information is derived from adult literature. We, therefore, analyzed our experience of CP to look for clinical profile and long-term outcome. Methods: From January 2003 to December 2015, 156 consecutive children (≤18 years) diagnosed as CP were included. Their clinical profile, management, and follow-up data were retrieved. Genetic markers (PRSS1, SPINK1, and CFTR) were studied in 40 idiopathic cases. Results: The median age of the patients was 13 [inter-quartile range (IQR): 10–14] years (93 males) and 134 (86%) were idiopathic. Genetic mutations were found in 22/40 (55%) idiopathic cases. All but two presented with pain abdomen (episodic pain in 93.6%) and symptom duration was 12 (IQR: 6–24) months. There were two subsets; calcific (CCP) 68 (43.5%) and non-calcific (NCCP) 88 (56.5%). In CCP group, significantly more children had Cambridge grade 5 magnetic resonance cholangiopancreatography changes, low weight Z-score, and had continuous pain more compared to NCCP group. Over a median follow-up of 23 (IQR: 8–45.5) months, more children in CCP group had complications. Endoscopic therapy (done for persistent pain in 40) relieved pain in 52.5% of cases while medical therapy did so in 36% of cases. Conclusion: Pediatric CP in Asia presents with episodic pain and genetic predisposition seems to be a major cause. There are two subsets; CCP and NCCP with former showing marked imaging changes, more often associated with malnutrition and complications. Endoscopic therapy for pain relief gives modest benefit but medical therapy is not encouraging.